ΛGR CENTENNIAL: COSMIC WEB IN DARK ENERGY BACKGROUND - Chernin, A. D. (Одеські астрономічні публікації, 2017)
The basic building blocks of the Cosmic Web are groups and clusters of galaxies, superclusters (pancakes) and ﬁlaments embedded in the universal dark energy background. The background produces antigravity, and the antigravity eﬀect is strong in groups, clusters and superclusters. Antigravity is very weak in ﬁlaments where matter (dark matter and baryons) produces gravity dominating in the ﬁlament internal dynamics. Gravity-antigravity interplay on the large scales is a grandiose phenomenon predicted by ΛGR theory and seen in modern observations of the Cosmic Web.